Efektivitas Transformasi Organisasi dan Manajemen Pemerintahan Serta Masyarakat yang Partisipatif Menuju Pelayanan Publik Unggul - Kusuma, Fanila Kasmita (Mahesa Research Center, 2024)
The transformation of government organizations is necessary to improve government performance. To achieve excellent public services, the community also plays an important role because the community is not only limited to receiving services but also as active partners in the process of planning, implementing, and evaluating policies. This research aims to describe the effectiveness of organizational transformation and government management in achieving excellent public services. The study will consider the impact of community participation in designing and improving policies as well as public services. This research uses descriptive qualitative methods and employs a questionnaire survey method as a research instrument. Qualitative research is a type of research that produces analysis without using statistical procedures or other quantitative methods. The results of this research indicate that organizational transformation and government management can improve the effectiveness and efficiency of public service delivery, while community participation can enhance the quality of public services. Active community participation in decision-making processes and government policy implementation allows the community to participate, provide input, and influence policy processes. Therefore, both factors must work simultaneously and support each other to realize excellent public services.